Understorey-overstorey biotic and nutrient interactions are key factors for Pinus pinaster growth and development under oligotrophic conditions - Vidal, David F.; Augusto, Laurent; Bakker, Mark R.; Trichet, Pierre; Puzos, Luc; Domec, Jean-Christophe (Scandinavian journal of forest research, 2021)
The main objective of this study was to examine the interactive effects of nutrient availability and understorey plants, including a nitrogen(N)-fixing shrub, on growth, physiology and survival of commercial maritime pines (Pinus pinaster Ait.). Three experimental sites within the Landes de Gascogne forest were installed in two wet moorlands (one dominated by gorse, a leguminous shrub and one by a perennial grass), and in one dry moorland dominated by ericaceous plants. In dry moorland, the ericaceous understorey increased pine mortality and decreased pine growth, suggesting a competition for water, the most limiting resource of this ecosystem. In wet moorland, a decrease in pine growth suggested a strong competition for soil resources, with or without phosphorus addition. In the other wet moorland dominated by gorse, pines responded to competition for light through stem elongation and self-pruning, but not by reducing growth. The intercropped gorse improved pine N-nutrition and trees acclimated to shrubs by growing more fine roots. Gorse had a positive effect on stomatal conductance during spring, while pine water status decreased moderately with increasing shrub competition during summer. Our results provide new understanding of the feasibility of using gorse as an intercropping N-fixing plant in managed forests, and revealed the structural and physiological trade-offs that exist between increasing N-availability and competition for water and light.